Cuba en la órbita de Francisco Curt Lange: un abordaje epistolar (1935-1975) - Boris Tejeda Suñol (2018)
This dissertation thesis analyzes the epistolary interactions between Francisco Curt Lange, a German musicologist who became Uruguayan citizen via naturalization, and some of the most distinguished representatives from the Cuban cultural, musicological, compositional and intellectual environment among 1935 to 1975. The strong intellectual network established by the researcher with his Antillean colleagues allows us to make a journey through some of the cardinal moments of the cultural and musical Cuban history. The several speeches and subjectivities that emerge from this epistolary dialogue let us to explore from new perspectives some of the ideoesthetic counterpoints from Cuban musical, political and cultural praxis during six decades. Likewise, in the correspondence interchange the transition between the republican contexts to the arrival of a transforming revolutionary process is clearly delineated. Curt Lange stands such as a lucid cultural intermediary between Cuba and the American geopolitical and cultural environment.